2012
DOI: 10.1073/pnas.1210182109
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional microfluidic model for tumor cell intravasation and endothelial barrier function

Abstract: Entry of tumor cells into the blood stream is a critical step in cancer metastasis. Although significant progress has been made in visualizing tumor cell motility in vivo, the underlying mechanism of cancer cell intravasation remains largely unknown. We developed a microfluidic-based assay to recreate the tumor-vascular interface in three-dimensions, allowing for high resolution, real-time imaging, and precise quantification of endothelial barrier function. Studies are aimed at testing the hypothesis that carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
695
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 764 publications
(744 citation statements)
references
References 44 publications
25
695
4
5
Order By: Relevance
“…Various microfluidic models have been developed for studying tumor angiogenesis (18), transition to invasion (19), intravasation (20), the role of interstitial flow (21) and matrix stiffness (22) on…”
mentioning
confidence: 99%
“…Various microfluidic models have been developed for studying tumor angiogenesis (18), transition to invasion (19), intravasation (20), the role of interstitial flow (21) and matrix stiffness (22) on…”
mentioning
confidence: 99%
“…Intravital multi-photon microscopy showed that tumor cell intravasation occurs through clusters of macrophages located on the abluminal side of the vessels [83]. Recently, Zervantonakis and colleagues described a three-dimensional micro-fluidic model to test tumor cell intravasation and endothelial barrier permeability [84]. They reported that macrophage production of tumor necrosis factor-α (TNF-α) resulted in endothelial barrier impairment and a higher intravasation rate.…”
Section: Intravasation Of Cancer Cellsmentioning
confidence: 99%
“…The heterogeneous Collagen I orientation was induced by internally developing strain fields due to the Matrigel volume swelling upon setting (25)(26)(27)(28)(29). Fig.…”
Section: Methodsmentioning
confidence: 99%